Penerapan Terapi Bermain Puzzle Pada Anak Pra Sekolah Yang Mengalami Kecemasan Akibat Hospitalisasi Di Bangsal Flamboyan 9 Rsud Dr. Moewardi - Eva Dwi Laksita Sari; Anjar Nurrohmah; Suciana Ratrinaningsih (An-Najat, 2024)
Background: Preschool is the period between the ages of 3-6 years. Children who are hospitalized will feel traumatic and full of stress when they are in hospital One type of game that is effective for preschool age children is puzzle play therapy. Puzzle is a game that requires patiece and concentration in putting it together, the child will also get used to being calm, patient and able to divert the child’s attention so that his mind is not too focused on treatment actions. Objective: To find out the results of the implementation of puzzle play therapy for preschool children (3-6 years) who experience anxiety due to hospitalization in the Flamboyan 9 ward RSUD Dr. Moewardi. Methods: The application was carried out using a case study descriptive method to 2 respondent of preschool children who experienced anxiety. Anxiety was observed before and after the puzzle play therapy. Results: Based on the result of the implementation that puzzle play terapy could reduce the anxiety level of children who owere hospitalization. Conclusion: Puzzle play terapi than can help reduce anxiety levels used as a technique to reduce anxiety in preschool children at the hospitalization in the Flamboyan 9 ward RSUD Dr. Moewardi.